A histopathologic study of salivary gland tumors in Kano, northern Nigeria - Ochicha Ochicha; Malami Sani; Mohammed Aminu; Atanda Akinfenwa (Wolters Kluwer Medknow Publications, 2009)
Significant differences in the global distribution of salivary gland tumors have been reported, but no formal study has been carried out here in Kano, the largest city in northern Nigeria. We therefore undertook this eight-year retrospective study of all histologically diagnosed salivary neoplasms at the histopathology laboratory of our referral teaching hospital in Kano. Seventy-eight salivary gland tumors were diagnosed during the eight-year study period accounting for 0.4% of all neoplasms. Benign tumors were more prevalent, comprising 56.4%, while malignancies were 43.6%. Pleomorphic adenoma and mucoepidermoid carcinoma were the commonest histological types constituting 48.7% and 23.1% respectively, while the most frequent sites were parotid, submandibular and minor salivary glands accounting for 49%, 26% and 24% respectively. As in most studies of black populations there were no adenolymphomas. Age distribution was bimodal with a benign peak in the third decade and a malignant peak in the sixth. Our findings were broadly similar to most other African reports but somewhat at variance with Western literature. Improved hospital attendance with more comprehensive reporting would yield more representative data.